Tracing the Circulation of Iconographic-style Red Ware in East-central Arizona. Issue 3 (2nd July 2020) - Van Keuren, Scott; Ferguson, Jeffrey R.
Abstract : The appearance of Fourmile Polychrome in the AD 1320s signaled a shift in the decorative layout, use, and perhaps even value of red-slipped pottery in east-central Arizona. Bowls were often painted with iconographic-style designs that diverged from the geometric imagery of earlier White Mountain Red Ware. The type was circulated through the region and even copied in some localities. The provenance of Fourmile Polychrome has remained a mystery due to the lack of research at late Silver Creek villages. We integrate results of neutron activation analysis (NAA) with a large corpus of existing NAA data to shed light on the production and circulation of this iconographic-style pottery. The results illuminate the social networks of ceramic circulation in the Silver Creek drainage and surrounding areas during the fourteenth century.